Dynamics of PCB exposure in the past 50 years and recent high concentrations in human breast milk: Analysis of influencing factors using a physiologically based pharmacokinetic model - Komprda, Jiří; Komprdová, Klára; Domínguez-Romero, Elena; Mikeš, Ondřej; Řiháčková, Katarína; Čupr, Pavel; Černá, Milena; Scheringer, Martin (The Science of the total environment, 2019)
In this study we reconstruct the long-term exposure of Czech mothers to polychlorinated biphenyls (PCBs) and determine the causes of high contamination of breast milk by indicator PCBs (iPCBs). A data set containing information from more than 1000 primiparous women from the Czech Republic was used, including iPCB concentrations in breast milk, individual physiology and living characteristics. The time series of PCB intakes for the whole period from the beginning of PCB production in 1958 until 2011 were reconstructed. We estimated the individual lifetime exposure of mothers for all iPCBs, i.e. congeners 28, 52, 101, 118, 138, 153 and 180, using a physiologically based pharmacokinetic (PBPK) model. Various model scenarios were investigated to determine the influence of physiology, age at delivery, past dietary exposure, and food composition on concentrations in breast milk for all iPCBs. The highest contributions to the presence of iPCBs in breast milk were observed for food composition. The main factor determining the concentration of higher-chlorinated PCBs (138, 153 and 180) was past exposure. The most important parameter for identification of children's postnatal exposure through breast milk was the time-span from the maximum of the exposure peak to the birth of the child. The current concentrations of iPCBs in breast milk in the Czech population are still high because the maximum of the exposure peak occurred more than 10 years later than in other European countries and was very broad, e.g. covered more than 10 years.
Keywords: dietární expozice; polychlorované bifenyly; Maternal Exposure; Humans; Polychlorinated biphenyls; mateřské mléko; Female; dospělí; Human biomonitoring; lidé; látky znečišťující životní prostředí; Breast milk; Adult; Dietary exposure; Environmental Pollutants; ženské pohlaví; Milk, Human; Dietary Exposure; Czech Republic; Physiologically based pharmacokinetic (PBPK) model; Česká republika; matka - expozice noxám; Intake; Polychlorinated Biphenyls